Makeover TV : Selfhood, Citizenship, and Celebrity - Weber, Brenda R., 1964- (Book collections on Project MUSE., 2009)
Examines the phenomenon of makeover television in order to explore how these shows participate in cultural debates about body modification, empowerment, gender roles, and personal responsibility.